Positional Relations of the Cervical Vagus Nerve Revisited. Issue 4 (1st February 2017) - Planitzer, Uwe; Hammer, Niels; Bechmann, Ingo; Glätzner, Juliane; Löffler, Sabine; Möbius, Robert; Tillmann, Bernhard N.; Weise, David; Winkler, Dirk
Abstract : Objectives: The cervical part of the vagus nerve (CVN) has become an important target for stimulation therapy to treat epilepsy and psychiatric conditions. For this purpose, the CVN is visualized in the carotid sheath, assuming it to be localized dorsomedially between the carotid artery (CA) and the internal jugular vein (JV). The aim of our morphological study was therefore to revisit the CVN relationships to the CA and JV, hypothesizing it to have common variations to this classical textbook anatomy. Materials and Methods: Positional relations of the CVN, CA and JV were investigated in the carotid sheath of 35 cadavers at the C3 to C6 level. Positional relations of the CVN, CA and JV were documented on the basis of a 3 × 3 chart. Results: Eighteen different arrangements of the CVN, CA and JV were observed. The typical topographic relationship of the CVN dorsomedially between the CA and JV was only found in 42% of all cases. The CVN was located dorsally or (dorso‐)laterally to the CA in 80% and dorsally or (dorso‐)medially of the JV in 96% of all cases. Conclusions: Classical textbook anatomy of the CVN is only present in a minority of cases. Positional variations in contrast to textbook anatomy are considerably more frequent than previously described, which might be a hypothetical morphological explanation for the lack of efficacy or side effects of CVN stimulation. Furthermore, the position of the CVN relative to the internal jugular vein is more consistent than to the CA.